Analysis of Efficiency and Quality Improvements Superior Products of Syariah General Insurance at Pt. Jasindo Syariah Kp. Medan - Sindi Novita Sari; Rahmi Syahriza (International Journal Labs, 2022)
Background: PT. Jasindo Syariah Kp. Medan is a type of sharia general insurance institution in Medan, North Sumatra that has superior products so that it can attract people to become insurance members. In order to continue to maintain the superior products of PT. Jasindo Syariah Kp. Medan, caused this institution to be able to compete with its competitors in the city of Medan. Objective: The purpose of this research is to understand how to improve the efficiency and quality of superior products of sharia general insurance in PT. Jasindo Syariah Kp. Medan Methods: Qualitative descriptive methods are applied, as well as applying interview methods and in-depth discussions, while data analysis techniques focus on qualitative methodological studies, for example, data reduction, presentation to conclusion drawing. Based on this research, data was produced that superior products are excellent in PT. Jasindo Syariah Kp. Medan is a property, especially fire products. Results: To improve the efficiency and quality of superior products, it is usually PT. Jasindo Syariah Kp. Medan considers in terms of market demand for fire products, improving services so that customers continue to choose superior products, namely fire products, as well as policies from the head office, DPS, and DSN-MUI considerations. Conclusion: At PT. Jasindo Syariah Kp. Medan, which is its superior product, is property products, especially fire products which have become excellent since early January 2021 until now. Data on the number of customers who choose fire products from PT. Jasindo Syariah Kp. Medan in the January-December 2021 period was 325 customers, while in the January-February 2022 period, there were 55 customers